The association between environmental design, crime in general and drug-related crime in Kota Bharu, Keloantan. - Ali, Shazwani Anis Amirah (Universiti Sains Malaysia, 2015)
This study was purposely to give information regarding the association between environmental design, crime and drug related crime in Kota Bharu, Kelantan. Crime and drug usage in our country was increasing year by year. This study is carried out to determine the perception of community towards drug usage and crime. This study was in form of test battery. Statistical analyses used in this study were descriptive statistic, One-way ANOVA, Kruskal-Wallis, Multiple Regression and Spearman-rank order Correlation. The objectives of this study were achieved. The relationships between environmental designs, crime in general and drug related crime in Kota Bharu, Kelantan were identified. Next, specific objectives of this study also have been determined. First null hypothesis was failed to reject while second null hypothesis was rejected. Third null hypothesis was also been rejected. For fourth null hypothesis, first part was rejected while part two was failed to reject. Lastly, the fifth null hypothesis also been rejected. There are several recommendation in this study such as citizen mobilization and after school recreation programs.